Tele-yoga for Chronic Pain: Current Status and Future Directions - Danielle C Mathersul PhD; Louise A Mahoney MS; Peter J Bayley PhD (SAGE Publishing, 2018)
Pain is a pervasive, debilitating disorder that is resistant to long-term pharmacological interventions. Although psychological therapies such as cognitive behavior therapy demonstrate moderate efficacy, many individuals continue to have ongoing difficulties following treatment. There is a current trend to establish complementary and integrative health interventions for chronic pain, for which yoga has been found to have exciting potential. Nevertheless, an important consideration within the field is accessibility to adequate care. Telehealth can be used to provide real-time interactive video conferencing leading to increased access to health care for individuals located remotely or who otherwise have difficulty accessing services, perhaps through issues of mobility or proximity of adequate services. This article assesses the current status and feasibility of implementing tele-yoga for chronic pain. Methodological limitations and recommendations for future research are discussed.